Determination of Total Germanium in Chinese Herbal Remedies by Square-Wave Catalytic Adsorptive Cathodic Stripping Voltammetry at an Improved Bismuth Film Electrode - Shangwei Zhong; Jiali Su; Liang Chen; Jiefeng Tong; Wenfang Jia; Xiangjun Li; Hong Zou (International Journal of Electrochemistry)
A catalytic adsorptive cathodic stripping voltammetric method on an improved bismuth film electrode (BiFE) for the determination of trace germanium in the presence of pyrogallol has been investigated. A well-defined and sensitive stripping peak of Ge(IV)-pyrogallol complex was observed at −0.79 V (versus SCE) in a 0.1 M acetate buffer solution (pH 4.8) at a deposition potential of −0.34 V. The reduction current is catalytically enhanced by adding KBrO3. The experimental variables and potential interference were studied. Compared with the BiFE plated in the solution prepared based on HAc-NaAc without trisodium citrate, the improved BiFE electrodeposited in the solution of HAc-NaAc containing trisodium citrate displayed a better electroanalytical performance for the determination of germanium(IV). Under the optimized conditions, the detection limit of Ge(IV) was 60 ng L−1, and the relative standard deviation (RSD) was 3.73% at 5 μg L−1 level (n=9). This method was successfully applied to determine the total germanium in several Chinese herbal remedies.